(untitled) (Research, Society and Development, 2021)
To know the perception of nursing students about Health Service Waste Management (GRSS). Descriptive qualitative study, developed in a public university in northeastern Brazil. The Focus Group (GF) technique was used with seven students from the fourth period of the undergraduate nursing course. They recognized the nurse as responsible for the Health Services Waste Management Plan (PGRSS) and highlighted Permanent Health Education (EPS) as a strategy to empower the team on the theme, which implies looking beyond health practices. The study found that there are weaknesses in the nursing education process in the face of the RSS theme. Possibly, this fact is associated with the phase of the course experienced by the students surveyed. Thus, these results deserve to be investigated in future studies, to deepen, seeking solutions to improve teaching on the subject.